Incidence and in-hospital complications of acute mitral regurgitation in the early phase of acute myocardial infarction in Erbil teaching hospital - Mawlood, Firaz Muhammad; Al-Othman, Abdulkareem A. (Zanco Journal of Medical Sciences (ZJMS), 2012)
Background and objectives: Acute mitral regurgitation is one of the mechanical complications of acute myocardial infarction. The aim of the study was to detect the incidence of ischemic mitral regurgitation and its effect on in-hospital complications in early phase of acute myocardial infarction. Method: The study sample consisted of 100 patients with first attack of acute myocardial infarction admitted to Coronary Care Unit in Erbil Teaching Hospital from October 2009 to May 2010.The patients categorized into: group-I which represent those without mitral regurgitation; group-II represent those with mitral regurgitation and the latter categorized patients with mild mitral regurgitation (group-IIA) and those with moderate-severe mitral regurgitation (group-IIB). Results: The incidence of acute mitral regurgitation among patients with acute myocardial infarction was 33%. Fourteen patient (42.42%) had mild and 19 (57.58%) had moderate-severe mitral regurgitation. Group-II patients were older (mean age: 65.4±10.76 years) than group-I (mean age 56±11), p value=0.01. Left ventricular systolic dysfunction among group-IIA, 9 patients (64.28%) and group-IIB, 16 patients (84.21%) were higher than group-I, 12 patients (17.91%), p=<0.001. Conclusion: Acute mitral regurgitation is common in early phase of acute myocardial infarction and it is strongly associated with left ventricular systolic dysfunction.